Gliding and Quasi-harmonic Tremor Behaviour of Raung Volcano: November 2014 Crisis Period Case Study - Ipmawan, Vico Luthfi; Brotopuspito, Kirbani Sri; Triastuty, Hetty (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.1.13-21The seismic activity of Raung Volcano was raised on 11 November 2014. As many as 1709 tremors were recorded followed by continuous tremors appearing in late November 2014. Quasi-harmonic and gliding tremors appeared in a spectrogram on 12 November 2014. The quasi-harmonic tremors refer to tremors that have no fully harmonic form in spectrum. The gliding harmonic tremors refer to harmonic tremors that have frequency jumps with either positive or negative increment. After signal restitution processing, the Maximum Entropy Spectral Analysis (MESA) method was applied in Raung recordings resulting the spectrum and the spectrogram of tremors. The quasi-harmonic tremors have the monotonic spectrum in its head and centre segment, and the harmonic one in its tails. There are twenty-four spectrums that show frequency changes between the monotonic and harmonic. The similarity between the fundamental frequency range of the monotonic and harmonic ones suggests that both signals are excited from a common resonator. The alternating of monotonic and harmonic respectively over this period is qualitatively similar with Julian’s synthetic time series about the nonlinear oscillator model. It is suggested that Raung Volcano magma pressure is sizeable to make a chaotic vibration. A pressure increasing in Raung magmatic conduit causes the increasing of P-wave velocity and makes a positive gliding frequency.